Antenatal care utilization and nutrition counseling are strongly associated with infant and young child feeding knowledge among rural/semi-urban women in Harari region, Eastern Ethiopia - Roba, Aklilu Abrham; Tola, Assefa; Dugassa, Desta; Tefera, Maleda; Gure, Tadese; Worku, Teshager; Ayele, Awugchew Teshome; Dasa, Tamirat Tesfaye; Workie, Hailemariam Mekonnen; Asfaw, Melese Mengistu; Asfaw, Abiyot; Mesfin, Firehiwot; et al. (Frontiers in Pediatrics, 2022)
There is a gap in evidence linking antenatal care (ANC) utilization, nutrition counseling, and knowledge of pregnant women about infant and young child feeding (IYCF), particularly in low-income settings. Therefore, this study aimed to identify the association between ANC follow-up and nutrition counseling with IYCF knowledge. A cross-sectional study was conducted among 390 pregnant women in the rural kebeles of the Harari region from January to June 2019. Data were collected using face-to-face interviews on tablet computers. Bivariate and multivariate logistic regression were employed. An adjusted odds ratio (with 95% CI) was used to determine the strength of association between IYCF knowledge with ANC follow-up and nutrition counseling by adjusting for educational status, occupation, gravida, and distance to the nearest health center. Overall, 54.4% [95% CI: 49.2, 59.2] of currently pregnant women were knowledgeable about IYCF of which only 20 % started ANC follow-up and 24.4% received nutrition counseling. Out of 288 multigravida women, only 51.4% had ANC follow-up during their last pregnancy. In the adjusted model, ANC follow-up during the current pregnancy (AOR 1.85, 95% CI 1.07–3.22), those who received nutrition counseling (AOR 1.92, 95% CI 1.09–3.38), literate in education (AOR 1.71, 95% CI 1.07–2.73), multigravida (AOR 1.96, 95% CI 1.12–3.43), and far from the nearest health center (AOR 0.95, 95% CI 0.93–0.97) were significantly associated with the mothers IYCF knowledge. Thus, health care providers should encourage mothers to attend ANC during pregnancy and provide nutrition counseling about the IYCF.